Frameworks for institutional audits for quality in South African higher education - Laetus Lategan (Acta Academica)
This paper attempts to establish che most suitable a system for institutional audits of higher education institutions in South Africa. It focuses on four areas: theory, philosophy, categories and practice. The paper argues chat self-evaluation is fundamental to the audit portfolio and the insricutional audits (theory). An approach is suggested where the focus is on procedures and mechanisms for quality instead of on quality per Je (philosophy). The author suggests eight categories for institutional audits: quality, policy implementation, evaluating mechanisms, teaching and learning, strategic management, student satisfaction, cost-effectiveness and external influences on the quality of the institutions.